2018
DOI: 10.1021/acs.orglett.8b00936
|View full text |Cite
|
Sign up to set email alerts
|

CuI-Catalyzed Asymmetric [3 + 2] Cycloaddition of Azomethine Ylides with Cyclobutenones

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in:Organic Letters 20.11 (2018)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 41 publications
1
20
0
1
Order By: Relevance
“…In 2018, an asymmetric [3 + 2] cycloaddition of azomethine ylides 133 and sterically demanding 2,3-diphenyl cyclobutenone 134 was developed by Adrio and Carretero with a chiral Fesulphos 135/Cu complex as the catalyst, delivering the 3-azabicyclo [3.2.0]heptane 136 in 64% yield and 84% ee (Scheme 26). 80 To avoid the steric interaction with the bulky t-Bu group, the cyclobutenone would approach the less hindered face of the tetrahedral chiral Cu complex I, thus affording the desired endoproduct in its current conguration.…”
Section: Difunctionalization Of All-carbon Tetrasubstituted Alkenesmentioning
confidence: 99%
“…In 2018, an asymmetric [3 + 2] cycloaddition of azomethine ylides 133 and sterically demanding 2,3-diphenyl cyclobutenone 134 was developed by Adrio and Carretero with a chiral Fesulphos 135/Cu complex as the catalyst, delivering the 3-azabicyclo [3.2.0]heptane 136 in 64% yield and 84% ee (Scheme 26). 80 To avoid the steric interaction with the bulky t-Bu group, the cyclobutenone would approach the less hindered face of the tetrahedral chiral Cu complex I, thus affording the desired endoproduct in its current conguration.…”
Section: Difunctionalization Of All-carbon Tetrasubstituted Alkenesmentioning
confidence: 99%
“…31 We have recently reported that the same catalytic system afforded excellent results in the reaction with cyclobutenones. 32 In this case, taking advantage of the ring strain of the dipolarophile sterically demanding substrates including -substitution at the cyclobutenone unit, provided the endo adducts with excellent diastereo and enantioselectivity (Scheme 9, Ab). 32 Zhang and co-workers extended the scope of the reaction to cyclohexenones with ImiFerroS 13 as ligand (up to 99% ee, Scheme 9, Ac).…”
Section: Chemcomm Accepted Manuscriptmentioning
confidence: 99%
“…32 In this case, taking advantage of the ring strain of the dipolarophile sterically demanding substrates including -substitution at the cyclobutenone unit, provided the endo adducts with excellent diastereo and enantioselectivity (Scheme 9, Ab). 32 Zhang and co-workers extended the scope of the reaction to cyclohexenones with ImiFerroS 13 as ligand (up to 99% ee, Scheme 9, Ac). 13 In 2005, our research group reported the catalytic asymmetric cycloaddition of methyl glycinate with nitrostyrene.…”
Section: Chemcomm Accepted Manuscriptmentioning
confidence: 99%
“…Other known methods for the synthesis of various 3‐azabicyclo[3.2.0]heptane derivatives include imide formation from cyclobutanedicarboxylic acid anhydride,, multicomponent cascade reactions of α,β‐unsaturated aldehydes, N ‐benzylaminocrotonate and secondary amines, and [3+2] cycloadditions. The latter approach is represented by reactions of cyclobutene derivatives with in situ generated oxazolium‐5‐oxides (Scheme , A ) or azomethine ylides, derived either from electrocyclic thermal aziridine ring‐opening ( B ) or deprotonation of iminium species ( C ).…”
Section: Introductionmentioning
confidence: 99%